2003
DOI: 10.1002/cncr.11766
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the impact of breast carcinoma screening in terms of tumor size and death rate

Abstract: BACKGROUND While the question of whether the trials of breast cancer screening have resulted in a reduction in breast cancer death has been the subject of much scrutiny, there has been less attention to the reduction in tumor size achieved by screening. METHODS Size data for invasive breast tumors were assembled from a variety of sources. The health consequences that can be expected from finding tumors of various sizes were determined using a recently developed mathematical method for relating tumor size to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 48 publications
2
23
0
4
Order By: Relevance
“…A previous study from Norway, where all screen and interval cancers in this study are included, shows close correlation between grading and lymph node involvement with tumor size [7]. The negative correlation between tumor size and survival is well known for invasive cases [9,18], and a mathematical model by Michaelson et al shows that the chance of dying from breast cancer increases by 1% for every additional mm of tumor diameter [19].…”
Section: Discussionsupporting
confidence: 57%
“…A previous study from Norway, where all screen and interval cancers in this study are included, shows close correlation between grading and lymph node involvement with tumor size [7]. The negative correlation between tumor size and survival is well known for invasive cases [9,18], and a mathematical model by Michaelson et al shows that the chance of dying from breast cancer increases by 1% for every additional mm of tumor diameter [19].…”
Section: Discussionsupporting
confidence: 57%
“…We have observed that, when information is available only on tumor size, a simple expression, the SizeOnly equation, accurately captures the relation between primary tumor size and lethality, as observed from our data on patients with breast carcinoma, renal cell carcinoma, and melanoma [1][2][3][4] (for the SizeOnly equation, see Equation 1 from the accompanying article 4 ). We also have observed that the relation between tumor size and the risk of cancer in the lymph nodes is captured well by a variant of the SizeOnly equation, the NodalSizeOnly equation (see Equation 1n in the accompanying article 4 ), as indicated by data from patients with breast carcinoma and patients with melanoma.…”
supporting
confidence: 61%
“…4,5 These values may be used in the ProbabilityEstimation equation (Equation 7) to estimate the value of the probability of the lethal spread of a cancer cell from a lymph node to the periphery, p node-to-periphery , if we also have information on the size of the cancer in the lymph nodes, N. To provide such information, we measured of the sizes of the cancer deposits in 50 positive lymph nodes from patients with melanoma and in 49 positive lymph nodes from patients with breast carcinoma (Tables 2 and 3). These measurements revealed an average size of the lymph node deposits of 28 mm 2 …”
Section: Spread Of Cancer Cells From a Lymph Node To The Periphery Cmentioning
confidence: 99%
“…14 Of great importance, yearly screening reduces the incidence, size, node metastatic rate, and mortality of cancers that appear as palpable masses between regularly screenings (interval cancers) compared to every-otheryear screenings, a factor not acknowledged by the US-PSTF report but well established in actual patient data, statistical modeling, and evaluating deaths from breast cancer. 11,[14][15][16][17] With screening every 2 years, the 25% of cancers that are interval cancers are similar to breast cancers diagnosed before mammography was used. 3,4,11 Just as ''yearly'' schedules actually occur at about 16-month median intervals, ''biennial'' screening will undoubtedly be closer to 30-month intervals as a result of patient forgetfulness, difficulty booking mammograms, and other factors.…”
Section: Yearmentioning
confidence: 99%